Rational Necessity in Hermeneutics: Exploring Al-Ghazali’s Hermeneutics Theory - Yassin, Derar Ali Bani; AlAhmad, Ahmad (Journal of Posthumanism, 2025)
This study explores interpretation as a pivotal element in early Islamic thought, particularly examining Al-Ghazali’s perspective on its role in shaping epistemological frameworks and rational traditions. Al-Ghazali’s views on interpretation, especially its interaction with theologians, Sufis, and philosophers, are central to understanding the relationship between reason and religious texts. The study also delves into the interpretive theory he proposed, along with the methodological principles he associated with it. It addresses the challenges of using reason to interpret religious texts amidst doctrinal and theoretical complexities, with Al-Ghazali attempting to create a theoretical balance between traditionalism and rationalism, influenced by his Sufi inclinations. The study finds that Al-Ghazali advocated a cautious approach to interpretation, stressing its necessity when texts appeared contradictory, and emphasizing rational evidence, although inconsistencies in his works suggest a blending of rationalist and mystical thought.